Evaluation of facial morphology and sagittal relationship between dental arches in primary and mixed dentition - Aline Traldi; Heloísa Cristina Valdrighi; Luciane Zanin de Souza; Silvia Amélia Scudeler Vedovello (Dental Press Editora, 2015)
OBJECTIVE: To assess facial morphology (Pattern) and sagittal relationship between dental arches (Class), and establish a potential association between them and the variables sex, age and ethnicity, among schoolchildren aged between 4 and 9 years old (mean age of 6.7 years) in primary and mixed dentitions.METHODS: The sample comprised 875 children (457 males and 418 females) attending schools in Descalvado, São Paulo, Brazil. An attempt was made with a view to establish a potential association between children's morphological features with sex, age and ethnicity.RESULTS: Descriptive analysis revealed a predominance of facial Pattern I (69.9 %) and Class I (67.4 %). Statistical tests (p < 0.001) showed that Class I was more frequent among Pattern I children, whereas Class II prevailed among Pattern II, and Class III was frequent among Pattern I and III children. Ethnicity was the only variable associated with facial pattern.CONCLUSIONS: Results suggest that facial pattern and sagittal relationship between dental arches tend to be correlated. Ethnicity was associated with facial pattern, with Pattern I being the most recurrent among Caucasians and facial Pattern II being recurrent among Afro-descendant subjects.